THE INFLUENCE OF SUBJECTIVE ATTITUDES AND NORMS ON MUSLIM CONSUMERS' PREFERENCES FOR ISLAMIC CLOTHING: - Rohman, Fathur; Masnita, Yolanda (Universitas Nusa Cendana, 2025)
This study aims to explore the influence of religiosity factors on Muslim clothing brand preferences. In the context of the growing Muslim fashion industry, a fundamental problem arises related to the importance of halal labels in consumer decision-making. Through the Theory of Planned Behavior (TPB) approach, this study shows that consumer attitudes towards Muslim clothing products, subjective norms in their environment, perception of behavior control, and the importance of halal labels play a key role in purchasing decisions. The study used a quantitative approach using a questionnaire to measure variables. The results showed that attitudes and subjective norms have a significant impact on consumers' preferences for Islamic clothing. To improve generalizability of the results, future research should consider a larger and more representative sample. Additionally, marketers should integrate religiosity and Muslim consumer preferences into their marketing strategies to better to the needs of Muslim consumers. Keywords: Theory of Planned Behavior; Perceived Behavioral Control; Halal Label; Brand Personality; Attitude; Subjective Norms; Perceived Importance; Purchase Intention